How to Use Early Childhood Educational Play Tools in Religious Moral Development Centers in Indonesia - Farihen, Farihen; Suharsiwi, Suharsiwi; Roshonah, Adiyati Fathu; Herwina, Herwina (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This study aims to evaluate the availability and use of Educational Game Tools (APE) in the center of religious moral development in Early Childhood Education Institution (PAUD) in Indonesia. The data used comes from the 2022 National APE Availability Dapodik system, which records information related to the availability of APE in various provinces. The findings show that APE that focuses on morals and religion (Imtaq) has a lower level of availability compared to other types of APE, with significant differences between regions. Central Java Province recorded the highest number of Imtaq APE, while provinces such as Gorontalo, Riau Islands, Maluku, and Southeast Sulawesi showed very limited availability. In addition, the results of the study showed that private kindergartens tend to have more Imtaq APE than public kindergartens, indicating different priorities in the procurement of learning tools. Various challenges, including teachers' lack of understanding of the use of APE in religious learning, limited school budgets, and the lack of policies supporting the procurement of APE based on morals and religion, were identified in this study. Although APE has a crucial role in learning religious values ​​from an early age, its availability still needs to be improved. Therefore, this study recommends policy support, training for teachers, and innovation in the development of APE Imtaq to improve the effectiveness of religious moral learning for early childhood in Indonesia